International Financial Reporting Standards and Value Relevance of Financial Information: An Empirical Evaluation of Selected Nigerian Listed Companies - Musa, Auwalu; Muhammad Tanimu, Ibrahim (International Journal of Accounting & Finance Review, 2017)
This study investigates the International Financial Reporting Standards (IFRS) and value relevance of financial information among Nigerian listed companies after the adoption of IFRS. 77 sample companies were randomly selected from the population. Data were collected from UUM-Data stream through the annual reports and accounts of companies, which consist of Stock price (dependent variable), Book value of equity and net income as (independent variables) for the year 2016. Ordinary Least Square Regression was the method used in analyzing the variables. The regression result revealed that there is a positive and significant relationship between book value of equity and net income on stock price. These reveal that the financial information of listed companies in Nigeria is more value relevant after the adoption of IFRS. In view of the findings, the study recommends that, Nigerian Stock Exchange should ensure that all listed companies are comply with the accounting framework issued by IFRS, in order to have full disclosure of their financial information.